2012
DOI: 10.1002/art.37737
|View full text |Cite
|
Sign up to set email alerts
|

Is the serum amyloid A we use really serum amyloid A? Comment on the article by Connolly et al

Abstract: The synthesis of asymmetric spherical nanoparticles has attracted great interest because their anisotropic structure can be used as unique building blocks for constructing advanced materials. In this article, we report the formation of hemispherical or truncated polystyrene/nanosaponite composite particles via one‐pot miniemulsion polymerization. It was found that the morphology of final composite latex particles strongly depends on the size of the nanoclay and its surface properties. Hemisphere or truncated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
1
8
1
Order By: Relevance
“…A similar finding was made in another study (van den Brand et al, 2013). Together, these results suggest the possibility that the chimeric rhSAA may have acquired additional cytokine-inducing activity because of the altered amino acid sequence.…”
Section: Major Functions Of Human Saa1supporting
confidence: 91%
“…A similar finding was made in another study (van den Brand et al, 2013). Together, these results suggest the possibility that the chimeric rhSAA may have acquired additional cytokine-inducing activity because of the altered amino acid sequence.…”
Section: Major Functions Of Human Saa1supporting
confidence: 91%
“…In most studies, a recombinant SAA was used. Christenson et al [242] and van den Brand et al [243] directly compared the recombinant SAA1α (rSAA1α) and the recombinant hybrid between SAA1α and SAA2β (rSAA) for their chemokine inducing capacity. More CXCL8 was induced when stimulating synovial fibroblasts or neutrophils with rSAA than with rSAA1α.…”
Section: Remarks and Conclusionmentioning
confidence: 99%
“…Nevertheless, an effect of contaminating LPS cannot be excluded, considering that TLR4 is one of the SAA receptors [64]. Of note, rhSAA1, prepared by the same manufacturer, has very low biologic activity in some of the functional assays [57], suggesting that it is possible to minimize LPS contamination in rSAA preparations to levels that do not affect significantly evaluation of SAA in functional assays. Studies that use 1 or more of these controls have shown that rhSAA still possesses biologic activities in the induction of cytokines and chemotaxis [25,28,31,43], the latter being less likely affected by LPS contamination as a result of the use of a G protein-coupled receptor, FPR2.…”
Section: Potential Involvement Of Saa In Inflammation and Unresolved mentioning
confidence: 99%
“…The exact reason for substituting these amino acids is unclear, but the resulting rhSAA becomes a hybrid of SAA1 and SAA2. In a letter to the editor of Arthritis & Rheumatism, van den Brand et al [57] compared this rhSAA hybrid with SAA1, which is also an E. coli-produced recombinant protein from the same commercial source. Their results indicate that the rSAA1 is much less effective in the induction of IL-8 transcripts and NF-kB activation.…”
Section: Potential Involvement Of Saa In Inflammation and Unresolved mentioning
confidence: 99%